KAJIAN PENENTUAN PRIORITAS RUANG TERBUKA HIJAU BERDASARKAN FENOMENA URBAN HEAT ISLAND DI KOTA CIREBON - Irland Fardani; Mohamad Rizalby Yosliansyah (Universitas Muhammadiyah Gorontalo, 2022)
Urban Heat Island (UHI) is characterized by an increase in surface temperature that occurs in downtown areas which is higher than in sub-urban areas. Cirebon City in 2018 - 2023 years has an increased population growth rate of 2.9% per year and ± 55% of built-up land. Cirebon city also one of the 9 cities in West Java where there has been an increase in temperature where the UHI phenomenon occurred in 1989 – 2021 years with the downtown and sub-urban areas having a surface temperature difference of 3°C. So it is necessary to have a study regarding determining the priority of green open space reduce the effect of UHI in Cirebon City. The research methodology used is Landsat 8 image processing and with helping of a Geographic Information System (GIS) to determine priority green open space locations. The parameters used are vegetation index, population density and comfort index. The purpose of this study is to determine the priority locations in increasing the area of green open space to reduce the UHI effect based on the level of suitability of the Cirebon City Rencana Detil Tata Ruang (RDTR). The results of the study show that areas that are not suitable according to the RDTR of Cirebon City are the top priority that needs to be done. The priority is reforestation covering an area of ± 2,481.22 ha around built-up land by modifying green open space in the form of implementing green infrastructure (GI).